Integrating Sentinel Surveillance Systems and Electronic Health Records: the case of Médicos-Sentinela and the National Health Service - Paixão, Hugo (2015)
Dissertação de Mestrado em Biomedical Engineering apresentada ao Instituto Superior Técnico, June 2015